Self-Efficacy in Parents and Children and its Relationship to Future Delinquent Behavior in Children - Walters, Glenn (My University, 2022)
A moderated mediation analysis was performed on 3,600 (1,829 boys and 1,771 girls) adolescents from the Longitudinal Study of Australian Children (LSAC). Results from a path analysis revealed that child self-efficacy mediated the relationship between mother control self-efficacy and child delinquency in girls but not in boys and that it mediated the relationship between father control self-efficacy and child delinquency in both boys and girls, with the effect being stronger in girls. Alternately, the direct effect from parental control self-efficacy to child delinquency was stronger in boys than girls. These results suggest that while girls may be discouraged from engaging in delinquency by modeling the self-efficacy of their parents, boys may more likely be dissuaded from delinquency by parenting factors other than modeling.
Youth and Society
Keywords: Adolescents and youth; Childhood and child development; Families and relationships